If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + y = -33 Solving 7x + y = -33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 7x + y + -1y = -33 + -1y Combine like terms: y + -1y = 0 7x + 0 = -33 + -1y 7x = -33 + -1y Divide each side by '7'. x = -4.714285714 + -0.1428571429y Simplifying x = -4.714285714 + -0.1428571429y
| 3x^2-18x+24=0 | | -6(-2+3g)= | | 11x-15=8x+3 | | 3(2x+1)+5=25 | | 3x=x+1 | | 12j=16j-128 | | -2.89=1.7m | | 3y+10=-23 | | 4x+3x+5+2=56 | | x^2-24x-25=0 | | 7+4k-6= | | 25=3(x-7)+5 | | 8(1+r)=1+8r | | 8n(6n+7)=5 | | 4r+3r= | | 13x^2-8x=0 | | (y-7)-(y+4)=8y | | 3x^2-75=0 | | 5(x-2)=7x | | 3(x+3)+5=25 | | 18.03=3g+3.72 | | 9b+7-1= | | 10x-16=74 | | 1.32g-8=0.58 | | 6(5+7z)= | | 9x+8=71 | | 42=8m-13m | | 2(-x-1)=2x-34 | | 3(x-1)+5=25 | | 5(-7z-6)= | | 49x^2-196=0 | | 5t-0=-3t+7 |